"Am I a Better Mother Than You?": Media and 21st-Century Motherhood in the Context of the Social Comparison Theory. (June 2015) - Chae, Jiyoung
This article explored the relationship between media exposure and contemporary motherhood based on social comparison theory (SCT). Based on previous studies indicating the flood of media discourse of celebrity moms and mothers' heavy reliance on the Internet, this article focused on celebrity mom and the Internet, respectively, as channels through which ideal motherhood is communicated. It was hypothesized that exposure to these channels would reinforce the ideology of contemporary motherhood characterized by intensive mothering, and promote comparison and competition . The questionnaire survey, conducted among 533 Korean mothers, revealed that exposure to celebrity mom discourse and online childrearing information was associated with the endorsement of the intensive mothering ideology, social comparison orientation (SCO), or competitiveness. Moreover, exposure to celebrity mom discourse was associated with the endorsement of intensive mothering ideology and SCO only among mothers who work outside the home, suggesting that celebrity moms serve as role models for them.